2017
DOI: 10.1111/anu.12482
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metabolic responses of juvenileMacrobrachium nipponenseto different dietary carbohydrate levels

Abstract: It remains controversial whether carbohydrate can be efficiently used by crustaceans.Six isonitrogenous and isolipid diets were formulated containing 50-350 g kg -1 corn starch and were fed to juvenile prawns (mean weight, 0.133 ± 0.003 g) for 56 days in five replicates. Prawns fed 50-150 g kg -1 corn starch attained significantly greater weight gain. Digestive enzyme activities were significantly affected by dietary corn starch level. Hepatopancreatic and muscle glycogen levels peaked in prawns fed 350 g kg -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…An appropriate level of carbohydrate may boost the antioxidative capacity and immune response in carp fish which may subsequently enhance the pathogen resistance and finally increase the growth. Similar results were observed in juvenile shrimps ( Ding et al., 2017 ) where the authors emphasize that the lower level of dietary carbohydrates resulted in a reduction of growth performance.…”
Section: Macronutrient Mediated Changes In the Expression Of Genessupporting
confidence: 80%
See 1 more Smart Citation
“…An appropriate level of carbohydrate may boost the antioxidative capacity and immune response in carp fish which may subsequently enhance the pathogen resistance and finally increase the growth. Similar results were observed in juvenile shrimps ( Ding et al., 2017 ) where the authors emphasize that the lower level of dietary carbohydrates resulted in a reduction of growth performance.…”
Section: Macronutrient Mediated Changes In the Expression Of Genessupporting
confidence: 80%
“…(2003) Carbohydrate dextrin, graded level (0 to 500 g/kg) juvenile black carp, liver tissue qPCR assay HEPC , TNF-α , IFN-α , LYZ , NRAMP , C3 Wu et al. (2016) Carbohydrate cornstarch, graded level (50 to 300 g/kg) juvenile prawns, muscle qPCR assay HK , PK , PYC , G6Pase Ding et al. (2017) Carbohydrate malto-dextrin humans, muscle qPCR assay MFN2 , GLUT4 , PGC-1α , UCP3 Dumke et al.…”
Section: Macronutrient Mediated Changes In the Expression Of Genesmentioning
confidence: 99%
“…Similar results were found in the spiny lobster J. edwwarsii ; in this other lobster species, lower values of α-amylase activity in the foregut and digestive gland were observed in individuals ingesting a formulated diet containing 36% wheat starch compared to those ingesting fresh food ( Simon, 2009c ). Differences in α-amylase activity induced by diets with different CHs inclusion have also been found in other crustaceans ( Ding et al, 2017 ). Taken together with previous results and those obtained in this work, it is demonstrated that spiny lobsters are relatively insensitive to CHs source in terms of α-amylase secretion to the gastric juice, but that they modify the amount of α-amylase secreted according to the amount of starch in the usual diet.…”
Section: Discussionmentioning
confidence: 59%
“…Santos et al (2014) identified proteases in the hepatopancreas (trypsin, leucine aminopeptidase and chymotrypsin) of adult males of this species by using specific substrates and inhibition tests. These are considered indirect methods to evaluate enzyme activity as previously reported in other congeneric species: M. tenellun (Montoya Martinez et al, 2018), M. rosenbergii (Wattanakul, Wattanakul, Thongprajukaew, & Muenpo, 2015) and M. nipponense (Ding et al, 2016).…”
Section: Introductionmentioning
confidence: 99%